Crop rotation XVIII. Effect of crop rotation systems on the yleld and on the intensity of root diseases of wheat. - Santos, Henrique Pereira dos; Reis, Erlei Melo; Pereira, Luiz Ricardo (Pesquisa Agropecuaria Brasileira, 2014)
Between 1979 and 1987, at the National Wheat Research Center-CNPT, in Passo Fundo, RS, Brazil, an experiment including two systems of rotation for wheat (Triticum aestivum L.) was carried out. Effetcs of crop rotation on wheat yield, root diseases severity, yield components, and on some agronomic characteristics of wheat plante were assessed. Systems of rotation were: 1) wheat, oats and flax, or; 2) wheat, lupins and rapeseed. A randomized block design with four replications was used and plots area was 120 m2. Wheat showed higher yield and plant hight when grown alter lupins and rapeseed than alter oats and flax. In both systems wheat presented stability of grain yield. It was concluded that there was no effect of the rotation systems on root rot diseases.